Biologics Prescribing for Rheumatoid Arthritis in Older Patients: A Single-Center Retrospective Cross-Sectional Study. Issue 2 (December 2015) - Morsley, Klara; Kilner, Thomas; Steuer, Alan
Abstract Introduction Appropriate medical treatment can reduce the morbidity and mortality associated with rheumatoid arthritis (RA). Studies have shown that older patients with RA may be treated less aggressively than their younger counterparts, despite evidence suggesting that biologic treatments may be safe and efficacious in older age groups. The aim of this study was to assess whether patient age was associated with biologic treatment for RA in a single center in the United Kingdom. Methods This was a retrospective cross-sectional analysis of clinic records for all patients with RA reviewed over 1 year in our center. Data were also collected on healthcare use in patients aged 65 years and older as a surrogate marker of comorbidity. Results In total, 856 patients with RA were identified, of which 22.8% were on biologic treatment. Patients on biologics were younger (mean age 58.9 years) compared to the mean age of all patients (61.4 years). Of patients aged less than 65 years, 27.2% were receiving biologic treatment, while only 15.2% of patients aged 65 years or older were on biologics. Increasing age was significantly associated with a lower likelihood of receiving biologic treatment. However, in patients 65 years or older, there was no significant difference in overall healthcare use between those on biologic treatment and those not. Patients treated with prednisolone were found to have a greater number of admissions. Conclusion In our center, older patients are less likely to receive biologic treatment than younger patients. Among older patients we found no difference in healthcare use between those treated with biologics and those not, suggesting similar levels of comorbidity. Potential contributors are discussed, but further assessment is required to determine the reasons for this observation.